ANALISIS MODELING LEAN MANAGEMENT DALAM UPAYA MENINGKATKAN KINERJA OPERASIONAL RUMAH SAKITPEMERINTAH - Pribadi, Fancholik Joko; Ratnawati, Tri (JEA17: Jurnal Ekonomi Akuntansi, 2020)
ABSTRACTIntroduce readers to Six Sigma techniques (DMAIC) as one of the lean management modeling that is possible to be used to improve the quality of products/services, processes and value added services that are sustainable in government hospital entities. The research design is qualitative descriptive with data obtained based on document search, literature studies and studying internal business processes in government hospitals. The method of improvement in Six Sigma for existing processes is called DMAIC and consists of five phases (Anderson et al., 2006 ) which aims to show the main prerequisites, strengths and limitations in their application. Government hospitals are a very complex service industry. Success in implementing a lean management model that can improve operational performance depends on the vision and mission, strategic plan, goals of each organization, ability to map problems and goals to be achieved. Empirically lean management modeling by applying DMAIC must find the right way and combination of methodologies in the implementation process. DMAIC is a systematic, fact-based approach that provides a results-oriented project management framework. There are 12 activity areas which are sources of waste where each waste has its own characteristic problems. Lean management with the implementation of the DMAIC model is one solution for government hospitals in the era of the implementation of JKN as an effort to improve efficiency, improve service quality and increase added value for patients. This paper provides general information about the strengths of DMAIC as lean management modeling. Considering that DMAIC is a complex methodology and requires the ability to map deep problems and sharpness in analysis, DMAIC cannot be applied simultaneously to all problems comprehensively but needs to be done step by step and identification of problem areas that are planned and measured so that their implementation does not fail in the middle Street. This paper presents a concise presentation of the main characteristics, strengths and limitations of the methodology presented. This finding can be used as strong information for management decisions in implementing lean management modeling called DMAIC as an effort to improve operational performance, especially in government hospitals. the Six Sigma model called DMAIC is a more complex methodology and has many requirements for success and therefore requires more time and resources for proper implementation. The ability to map deep problems and sharpness in analysis is needed